2021
DOI: 10.1002/nbm.4637
|View full text |Cite
|
Sign up to set email alerts
|

Uneven metabolic and lipidomic profiles in recovered COVID‐19 patients as investigated by plasma NMR metabolomics

Abstract: COVID‐19 is a systemic infectious disease that may affect many organs, accompanied by a measurable metabolic dysregulation. The disease is also associated with significant mortality, particularly among the elderly, patients with comorbidities, and solid organ transplant recipients. Yet, the largest segment of the patient population is asymptomatic, and most other patients develop mild to moderate symptoms after SARS‐CoV‐2 infection. Here, we have used NMR metabolomics to characterize plasma samples from a coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
39
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 33 publications
7
39
0
2
Order By: Relevance
“…Our study found a significant, and very relevant, increase in serum long-chain TG concentrations in COVID-19-positive compared with COVID-19-negative patients. TG are carried in the circulation packed in the very-low density lipoproteins (VLDL), and studies agree in that the levels of triglycerides, VLDL, and polyunsaturated fatty acids are increased in COVID-19 and Ebola virus disease [23] , [58] , [59] , [60] . Therefore, this elevation in long-chain TG concentrations could be related to the immune response, although the mechanisms behind its deregulation are not well elucidated.…”
Section: Discussionmentioning
confidence: 94%
“…Our study found a significant, and very relevant, increase in serum long-chain TG concentrations in COVID-19-positive compared with COVID-19-negative patients. TG are carried in the circulation packed in the very-low density lipoproteins (VLDL), and studies agree in that the levels of triglycerides, VLDL, and polyunsaturated fatty acids are increased in COVID-19 and Ebola virus disease [23] , [58] , [59] , [60] . Therefore, this elevation in long-chain TG concentrations could be related to the immune response, although the mechanisms behind its deregulation are not well elucidated.…”
Section: Discussionmentioning
confidence: 94%
“…Among the 22 metabolites, kynurenic acid, 1-methyladenosine, phosphatidylethanolamines (PE), and ceramides (Cer) were found increased. Instead, Bizkarguenaga et al [ 57 ] found by NMR that recovered COVID-19 patients between 3 and 10 months after diagnosis showed increased plasma levels of cholesterol, triglycerides (TG), and phospholipids. Finally, Khodadoust [ 58 ], through lipidomic analysis of 52 plasma samples, detected lipids belonging to the ceramide class increased by a 400-fold in infected patients.…”
Section: Metabolomics Of Covid-19mentioning
confidence: 99%
“…With the same approach one can simultaneously quantify the lipoprotein class-specific concentrations of cholesterol, phospholipids and triglycerides, thus providing an exhaustive description of the lipoproteome in addition to the NMR-detectable fraction of the metabolome [ 25 ]. S1 and S2 Figs summarize the main results of NMR metabolomic studies on the serum or plasma of COVID-19 patients in comparison with control populations [ 6 14 ].…”
Section: Introductionmentioning
confidence: 99%